2014
DOI: 10.14423/smj.0000000000000173
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index and Waist Circumference with Subclinical Atherosclerosis in Retired NFL Players

Abstract: In retired NFL players both BMI and WC were associated with CAC. Higher BMI may be associated with an increasing trend for the presence of CAC independent of WC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…However, when they retire, many will increase their body fat levels substantially, while maintaining their high BMI. A study of 926 retired NFL players whose mean BMI was 30 and mean waist circumference was 40 showed that 61% were at risk for atherosclerosis; the most at risk being those with larger waist circumference (10). A number of other studies have reported various discrepancies between BMI and the accumulation of body fat in various other populations (10, 3537).…”
Section: Problems With Bmi As a Measure Of Obesitymentioning
confidence: 99%
See 4 more Smart Citations
“…However, when they retire, many will increase their body fat levels substantially, while maintaining their high BMI. A study of 926 retired NFL players whose mean BMI was 30 and mean waist circumference was 40 showed that 61% were at risk for atherosclerosis; the most at risk being those with larger waist circumference (10). A number of other studies have reported various discrepancies between BMI and the accumulation of body fat in various other populations (10, 3537).…”
Section: Problems With Bmi As a Measure Of Obesitymentioning
confidence: 99%
“…A study of 926 retired NFL players whose mean BMI was 30 and mean waist circumference was 40 showed that 61% were at risk for atherosclerosis; the most at risk being those with larger waist circumference (10). A number of other studies have reported various discrepancies between BMI and the accumulation of body fat in various other populations (10, 3537). Clearly, BMI has limited relevance for assessing accurate markers of body composition and body fat distribution, which are important signs of metabolic health (1).…”
Section: Problems With Bmi As a Measure Of Obesitymentioning
confidence: 99%
See 3 more Smart Citations